Does Fed policy reveal a ternary mandate? - Joe Peek; Eric S. Rosengren; Geoffrey M. B. Tootell (Federal Reserve Bank of Boston, 2016)
This paper examines the role of financial instability in setting monetary policy. The paper begins with a model that examines the interaction of monetary and regulatory policy. It then empirically tests whether financial instability has affected monetary policy. One important innovation is to construct a measure of financial instability directly related to the FOMC financial instability concerns expressed in FOMC meeting transcripts. We find that, even after controlling for forecasts of inflation and unemployment, the word counts of terms related to financial instability do correlate with monetary policy decisions. Thus, the FOMC not only "talks the talk" about financial stability, but it "walks the walk."
Keywords: E52; E58; E44; 330